Transient entropy analysis of the magnetohydrodynamics flow of a Jeffrey fluid past an isothermal vertical flat plate - Kumar, Mahesh; Reddy, G Janardhana; Dalir, Nemat (Pramāṇa, 2018)
This study presents the analysis of entropy generation concept for unsteady magnetohydrodynamics Jeffrey fluid flow over a semi-infinite vertical flat plate. This physical problem is constituted by transient coupled highly nonlinear equations and is evaluated numerically by using an implicit scheme. The average values of wall shear stress and Nusselt number, entropy generation number and Jeffrey fluid-flow variables are analysed for distinct values of physical parameters at both transient and steady states. The results show that the time needed for achieving a steady state pertaining to the temperature and velocity gets augmented with the increased values of Jeffrey fluid parameter. The results also specify that the entropy generation number increases with the increasing values of Jeffrey fluid parameter, group parameter and Grashof number while the opposite trend is seen for the magnetic parameter.